The influence of social media marketing on customer buying behavior in Kota Kinabalu - Wang Jian (2016)
Nowadays, any marketer or business owner should understand the importance of online marketing. Doing a business on the website signifies leveraging social media to generate a lot of buzz in relation to a brand. Social media platforms offer huge possibilities for maintaining relationships with customers in an internet environment. This study aims to analyses the factors that could conceivable influence customer buying behavior in Malaysia. The constructs used to measure the customer buying behavior in this study are information, design, website speed, and price. This study adopts quantitative approach by distributing the questionnaire to the respondent. Online questionnaire to collect data was also conducted in this study. The results in this study suggested that, from four hypotheses, only one was supported which is information plays a significant role on customer buying behavior. The other three were not supported. Some of the not supported hypotheses in this study were supported in previous studies. The contributions of this study were divided into two sections- theoretical implication and contribution in managerial field. This study hopes to continue to marketers in terms of significant factors for social media business. The self-administered questionnaires will be distributed among 200 respondents in Sabah.